Accurate line intensities of methane from first-principles calculations. (October 2017) - Nikitin, Andrei V.; Rey, Michael; Tyuterev, Vladimir G.
Highlights: Theoretical calculation of methane spectral line intensities was reported. Detailed comparison of calculated and observed intensities was done. First-principle dipole moment surfaces were compared. Abstract: In this work, we report first-principle theoretical predictions of methane spectral line intensities that are competitive with (and complementary to) the best laboratory measurements. A detailed comparison with the most accurate data shows that discrepancies in integrated polyad intensities are in the range of 0.4%–2.3%. This corresponds to estimations of the best available accuracy in laboratory Fourier Transform spectra measurements for this quantity. For relatively isolated strong lines the individual intensity deviations are in the same range. A comparison with the most precise laser measurements of the multiplet intensities in the 2ν3 band gives an agreement within the experimental error margins (about 1%). This is achieved for the first time for five-atomic molecules. In the Supplementary Material we provide the lists of theoretical intensities at 269 K for over 5000 strongest transitions in the range below 6166 cm −1 . The advantage of the described method is that this offers a possibility to generate fully assigned exhaustive line lists at various temperature conditions. Extensive calculations up to 12, 000 cm −1 including high-T predictions will be made freely available through the TheoReTS information system (http://theorets.univ-reims.fr, http://theorets.tsu.ru) that contains ab initio born line lists and provides a user-friendly graphical interface for a fast simulation of the absorption cross-sections and radiance.